Steady-state and lifetime fluorescence studies of pyrene probes in model membranes: trailblazing analysis of two-dimensional quenching kinetics with nitroxide probes and excimer formation - Manuel, Miguel Alexandre da Silva (2016)
Tese de doutoramento, Ciências Biológicas (Bioquímica), Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2013